Effect of Mackerel (Scomberomorus Commerson) Bone-Derived Gelatin on Alum Performance in Coagulation–Flocculation Processes - Ramadhan, Aditya Nur; Zaharah, Titin Anita; Sayekti, Endah (POSITRON, 2026)
Mackerel fish bones are commonly discarded as waste and may contribute to environmental pollution. This study aimed to extract gelatin from mackerel fish bones and evaluate its use as a coagulant aid with alum for the removal of organic matter and total suspended solids (TSS) from peat water. Gelatin was extracted and its functional groups were characterized using Fourier transform infrared (FTIR) spectroscopy. Treatment performance was evaluated through jar test experiments by varying Gelatin dosage (2, 4, 6, 8, and 10 g/L) and pH (4–8). Organic matter concentration was determined using the permanganometric titration method, while TSS was measured using the nephelometric method. The gelatin yield was 2.45%, and FTIR analysis confirmed the presence of amide functional groups, indicated by N–H stretching at 3353 cm⁻¹. The addition of gelatin enhanced alum performance, with optimal conditions at a dosage of 8 g/L and pH 7, achieving removal efficiencies of 89.3% for organic matter and 87.8% for TSS with a sedimentation time of 15 minutes. These findings demonstrate the potential of fish bone–derived gelatin as an effective and sustainable coagulant aid for peat water treatment.